Strategi Pemasaran Menggunakan Metode STP (Segmenting, Targeting, Positioning) pada Industri Frozen Food - Sakina Zakaria; Putri Wulan Cahyani; Veronika Wulan Dari; Indah Setyaning Ari; Candra Wardana; Evi Yuliawati; Suparto Suparto (Prosiding SENASTITAN: Seminar Nasional Teknologi Industri Berkelanjutan, 2023)
Nowadays, business competition is getting tougher, so companies are required to make good strategies and in accordance with the wishes of the company, so that companies can still survive. A good company is a company that wants its sustainable existence and get the best position in the market rather than just survive. Therefore, companies are not only trying to get new customers but also trying hard to retain the customers they have got. One of the growing industries is the frozen food industry. Currently the frozen food industry or Frozen Food is innovating by presenting several product variants that are in accordance with market desires. The results of this study Naisha Frozen Food market segments for teenagers, namely between 17-38 years old with middle and down social class. Moreover today, business competition is getting tougher, so companies are required to make good strategies and in accordance with the wishes of the company, so that companies can still survive. A good company is a company that wants its life to be sustainable and get the best position in the market rather than just surviving. Therefore, companies are not only trying to get new customers but also trying hard to retain the customers they have got. One of the growing industries is the frozen food industry. Currently, the frozen food industry is innovating by presenting several product variants that are in line with market demands. Therefore, this research is expected to provide benefits to Naisha Frozen Food in terms of an overview of business development and provide improvements towards increasing turnover or income in the future. Using the STP (Segmenting, Targeting, Positioning) method is expected to have a positive impact on Naisha Frozen Food to increase sales turnover.Keywords: Frozen Food, Increased Turnover, STP (Segmenting, Targeting, Positioning)